2014
DOI: 10.1136/tobaccocontrol-2014-051930
|View full text |Cite
|
Sign up to set email alerts
|

'It will harm business and increase illicit trade': an evaluation of the relevance, quality and transparency of evidence submitted by transnational tobacco companies to the UK consultation on standardised packaging 2012

Abstract: IntroductionTransnational tobacco companies (TTCs) submitted evidence to the 2012 UK Consultation on standardised packaging (SP) to argue the policy will have detrimental economic impacts and increase illicit tobacco trade.MethodsA content analysis of the four TTC submissions to the consultation assessed the relevance and quality of evidence TTCs cited to support their arguments. Investigative research was used to determine whether the cited evidence was industry connected. Fisher's exact tests were used to co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 43 publications
3
55
0
Order By: Relevance
“…Searches generated ten relevant empirical studies 21,30,[32][33][34][35][36][37][38][39] : three were qualitative studies (two reporting focus group research with young adult smokers in Scotland 30,32 , and in-depth interviews with retailers in New Zealand 39 ); three were content analyses (of online commentary on tobacco packaging in Australia 33 , UK press coverage of the illicit tobacco trade 34 and the four TTC submissions to the consultation in the UK 35 ); two were cross sectional surveys (of illicit tobacco use following introduction of standardized packaging in Australia) 36,37 ; and two were before and after studies (one of availability of illicit tobacco in small retail outlets 38 and one empty-pack survey before and after the introduction of standardized packaging in Australia) 21 . See Table 2 for a summary of included studies.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Searches generated ten relevant empirical studies 21,30,[32][33][34][35][36][37][38][39] : three were qualitative studies (two reporting focus group research with young adult smokers in Scotland 30,32 , and in-depth interviews with retailers in New Zealand 39 ); three were content analyses (of online commentary on tobacco packaging in Australia 33 , UK press coverage of the illicit tobacco trade 34 and the four TTC submissions to the consultation in the UK 35 ); two were cross sectional surveys (of illicit tobacco use following introduction of standardized packaging in Australia) 36,37 ; and two were before and after studies (one of availability of illicit tobacco in small retail outlets 38 and one empty-pack survey before and after the introduction of standardized packaging in Australia) 21 . See Table 2 for a summary of included studies.…”
Section: Resultsmentioning
confidence: 99%
“…There were few studies examining tobacco standardized packaging and illicit trade and those that were available were generally not of high quality. We identified ten relevant empirical studies which examined standardized packaging and illicit tobacco 21,30,[32][33][34][35][36][37][38][39] . Five studies reported smokers did not intend to 30,32 or actually 21,36,37 purchase more illicit tobacco following standardized packaging although one 33 suggested a small number of responders to online news felt smokers In 179 (59%) of the shops the secret shopper then asked the retailer about the availability of unbranded, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations